Asymmetric synthesis of α-alkylated aldehydes using chiral enamines - Kaka, N; Naeem Kaka (2008)
Direct generation of enantioenriched mono-α-alkylated aldehydes by intermolecular nucleophilic substitution is a general and long-standing problem in synthesis, and is of importance due to the diverse reactions such aldehydes undergo for introducing asymmetry into molecules. The work described in this thesis initially details the development of the first lithium amide capable of efficiently converting terminal epoxide into enamine functionality, where the latter also demonstrates effective C-alkylation activity. Not only addition to Michael acceptors, but more notably substitution using activated organohalides (α-bromoacetates, benzyl, allyl and propargyl bromide) gave the corresponding α-substituted aldehydes in good to excellent yields. Alkylation with propargyl bromide yielded only the propargyl-substituted aldehyde with none of the corresponding allene observed; this result shows that N-alkylation followed by [3,3] sigmatropic rearrangement is not occuring. Importantly, a range of short-, longer-chain and secondary unactivated alkyl iodides also proved viable. Significantly, with chiral lithium amides, the corresponding chiral enamines could be alkylated with strongly electrophilic benzyl, allyl and propargyl (no allene seen) bromides in very good yields, and with short chain alkyl iodides – MeI and EtI in satisfactory yields, to provide the first direct access to α-alkylated aldehydes with high asymmetric induction by intermolecular nucleophilic substitution.